CONSUMER ACCEPTANCE TO FRIED TILAPIA BABY FISH (Oreochromis nilotis) IN DIFFERENT SIZES - Nur Asia; Suparmi '; Sumarto ' (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2016)
The purpose of this study was to determine the consumer acceptance of the product fried tilapia baby fish in different sizes and find out the nutritional value of the product fried baby fish tilapia (Oreochromis nilotis). This research used experimental method and was designed as non-factorial completely randomized design with 3 treatments and 3 replications, namely P1 (tilapia baby fish sized of 3-4 cm), P2 (baby tilapia sized of 5-6 cm), and P3 (baby tilapia sized of 7-8 cm). Parameters measured were organoleptic test, the value of crispness, and proximate composition of the fried tilapia baby fish. The results showed that the fried tilapia baby fish in size of 3-4 cm was the most preferred by consumers. Fried tilapia baby fish contained of 20,27% protein, 9.73% fat, 23.62% moisture, and 2.79% with the value of crispness 97.5%.Key words: Consumer acceptance, fish fried, size, nutrition, tilapia